The Effect of Olive Oil, VCO, and Corn Oil with Adeps Lanae and Vaselin Alba Variation to Physical Characteristic of Methyl Salicylic Stick Balm - Anisa Amalia (LPPM - Universitas Muhammadiyah Banjarmasin, 2020)
AbstractThe physical characteristic of stick balm have been affected the consistency and comfortness at the time of used. Components that affected the physical properties of stick balm were components of fats and oils. Fat used were adeps lanae and vaseline alba, as it can prevented the tendency to split up oil. The components of the oil used were the VCO which had saturated fatty acids, olive oil and corn oil which had not saturated fatty acids which could affected the melting point and hardness. Based on the foregoing, the comparison of oil type with variations of adeps lanae and vaseline alba carried out towards the physical characteristic of stick balm methyl salicylate. The purpose of this research was to knew the effect of olive oil, corn oil and VCO with variations of adeps lanae and vaseline alba towards the physical properties of stick blam. Adeps lanae and vaselin alba concentration was 10%. Characterization performed on stick balm which included analysis of organoleptics, the melting point and hardness. Results indicate formula with adeps lanae more colored yellow. Homogeneity test of each formula showed that the stick balm was homogeneous. On the hardness and melting point assay, the results qualified on 3.3 mm - 4.16 mm and 51.25 0C - 56.52 0C. A summary of this research was the used of adeps lanae with VCO delivered the highest melting point on 56.52 ºC and the most violent both with translucent 3.33 mm depth. Keywords: physical characteristic, stick balm, a type of oil, variations of adeps lanae and vaseline alba